Analysis of External Surface Irregularities on Fukushima-Derived Fallout Particles - Martin, Peter George; Satou, Yukihiko; Griffiths, Ian; Richards, David; Scott, Thomas (Frontiers in Energy Research, 2017)
Three large high radioactivity particulate fragments, each several 100 μm in diameter, have been recovered from the region immediately surrounding the Fukushima Daiichi Nuclear Power Plant. Through the application of high-resolution electron and ion-beam methods, this work has sought to investigate the structure and composition of this fibrous surface morphology. By evaluating this, a potential material source can be determined, alongside important information relating to the conditions/events at the time of the reactor explosions and catastrophic release of radioactive materials. The results of this study show that the fibrous features associated with these large radiocesium-containing particles share a common elemental composition. With respect to the surrounding particle, the fibers are enriched in Si, Cl, and Fe, while depleted in both Zn and Al. Based on composition, these fibers are ascribed to thermal insulating material used within the plant, which was sufficiently heated during the loss of coolant incident at the plant to be incorporated into the molten ejecta material that rapidly solidified upon quenching in air. Elemental analysis of these fibers does not reveal any evidence of leaching or the presence of actinide materials.